2012
DOI: 10.1245/s10434-012-2669-8
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CEA Levels and Low Distance of the Tumor from the Anal Verge are Predictors of Incomplete Response to Chemoradiation in Patients with Rectal Cancer

Abstract: Very low tumors with a high serum CEA are very unlikely to reach a CPR. The predictive value of these easily available clinical factors should not be underestimated, and better therapeutic strategies for these tumors are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 45 publications
2
54
1
Order By: Relevance
“…Other trials explored the same hypothesis using 5 ng/mL as a cutoff value, and confirmed pretreatment CEA as a valuable predictor of tumor response. [78][79][80][81] Wallin et al 82 investigated a different cutoff value, 3.4 ng/mL, but again demonstrated the predictive value of low baseline CEA in terms of significantly higher pCR rates, especially in the group of nonsmokers (P ¼ .002). In a smaller trial Perez et al 83 did not observe any correlation between pretreatment CEA levels and pCR or survival.…”
Section: Carcinoembryonic Antigenmentioning
confidence: 99%
“…Other trials explored the same hypothesis using 5 ng/mL as a cutoff value, and confirmed pretreatment CEA as a valuable predictor of tumor response. [78][79][80][81] Wallin et al 82 investigated a different cutoff value, 3.4 ng/mL, but again demonstrated the predictive value of low baseline CEA in terms of significantly higher pCR rates, especially in the group of nonsmokers (P ¼ .002). In a smaller trial Perez et al 83 did not observe any correlation between pretreatment CEA levels and pCR or survival.…”
Section: Carcinoembryonic Antigenmentioning
confidence: 99%
“…In rectal cancer there are several studies analyzing changing CEA levels in relation to preoperative CRT. High CEA levels pre- as well as post-therapeutical were associated with a poorer prognosis [10,11,12,13,14,15,16]. However, the clinical use of CEA as a molecular biomarker to predict pathologic complete response has its limitations and is controversially discussed [11,17].…”
Section: Introductionmentioning
confidence: 99%
“…We could select treatment plan or modality based on predictions of response. Many studies focused on clinical factors and molecular profile of cancer lesion and confirmed the association of biomarker with tumor response [3,4]. Immunological host status also influenced tumor response [5].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical factors such as carcinoembryonic antigen (CEA), distance from the anal verge, and molecular profile were associated with tumor response [3,4]. Recently, in addition to the clinical factors, the relationship between host immunity and tumor response was studied.…”
Section: Introductionmentioning
confidence: 99%